Upscaling bean-based recipes: Training 1000+ trainers in Malawi. Government and NGOs collaborate to incorporate beans to enhance quality of nutrition programs - Munthali, Justice; Birachi, Eliud (2024)
As part of efforts to promote common beans in Malawi, CIAT/PABRA and partners has been implementing research-based nutrition-sensitive agriculture interventions, conducting nutrition studies to design, implement and upscale nutrition-sensitive solutions. These solutions included the participatory development of nutrition education and promotional materials, training extension workers, implementing community engagement initiatives, developing policy briefs, and preparing reports and peer reviewed papers. As a result, the government and other partners are promoting, adopting and upscaling bean-based recipes to sustainably diversify Malawi’s monotonous diets.